Sensory and Motor Function, Pain, and Health Status in Children with Arthrogryposis and Myelomeningocele - Åsa Bartonek; Marie Eriksson (Children)
Background/Objectives: Proprioception and sensory disorders have been reported in children with arthrogryposis multiplex congenita (AMC) and myelomeningocele (MMC), but valid and reliable assessment tools are limited in accurately identifying the sensory aspects of motor disorders. This study aimed to investigate the somatosensory status in the feet and legs. An additional purpose of this study was to explore pain, skin irritations, and health status. Methods: Nineteen children with AMC, twenty-three with MMC, and twenty-two typically developing (TD) children (7–18 years old) were tested using a somatosensory test battery in ankle kinesthesia and in identifying four different types of floors. Results: In the AMC and MMC groups, the threshold to perceive the somatosensory stimuli was not achieved by all participants. MMC participants perceived somatosensory stimuli less than TD participants in all tests, with a higher level of the lesion and more affected ambulation. The MMC group identified one floor significantly less often than the TD group. The AMC group performed better than the MMC group in two-point discrimination, vibration sensation, and some light-touch pressure tests. There were no differences among the TD, AMC, and MMC groups in ankle kinesthesia. Pain was reported by four (21%) subjects in the AMC group and five (22%) in the MMC group, and skin irritations were reported by three (13%) participants in the MMC group. There was no difference among the TD, AMC, and MMC groups in health status as reported using the EQ-5D-Y visual analog scale. Conclusions: Although differences in sensory aspects were the most evident between the groups, assessments of activity and participation levels in the rehabilitation of children with disabilities are also recommended.